Human Brain Organoids: Why There Can Be Moral Concerns If They Grow Up in the Lab and Are Transplanted or Destroyed - Lavazza, Andrea (Cambridge quarterly of healthcare ethics, 2023)
Human brain organoids (HBOs) are three-dimensional biological entities grown in the laboratory in order to recapitulate the structure and functions of the adult human brain. They can be taken to be novel living entities for their specific features and uses. As a contribution to the ongoing discussion on the use of HBOs, the authors identify three sets of reasons for moral concern. The first set of reasons regards the potential emergence of sentience/consciousness in HBOs that would endow them with a moral status whose perimeter should be established. The second set of moral concerns has to do with an analogy with artificial womb technology. The technical realization of processes that are typically connected to the physiology of the human body can create a manipulatory and instrumental attitude that can undermine the protection of what is human. The third set concerns the new frontiers of biocomputing and the creation of chimeras. As far as the new frontier of organoid intelligence is concerned, it is the close relationship of humans with new interfaces having biological components capable of mimicking memory and cognition that raises ethical issues. As far as chimeras are concerned, it is the humanization of nonhuman animals that is worthy of close moral scrutiny. A detailed description of these ethical issues is provided to contribute to the construction of a regulative framework that can guide decisions when considering research in the field of HBOs.